Maternal and Fetal Anaesthesia for Fetal Surgery. Issue 1 (23rd March 2022) - Dick, J.R.; Wimalasundera, R.; Nandi, R.
Abstract : ( Anaesthesia . 2021;76(suppl 4):63–68) Over the past 3 decades, great advances have been made in fetal surgery. While many procedures require only local anesthesia, additional maternal and/or fetal anesthesia can be needed. Multidisciplinary planning is needed to ensure success in these procedures. This article reviews three fetal surgical procedures and the anesthetic considerations for each.